The profile of the skilled reader: An investigation into the role of reading enjoyment and student characteristics - Rogiers, Amelie; Van Keer, Hilde; Merchie, Emmelien (International journal of educational research, 2020)
•A positive relationship was found between reading enjoyment and reading comprehension.•Girls, higher SES students and students in the academic track score higher on both reading enjoyment and comprehension.•Students in the vocational track score the lowest on reading enjoyment and reading comprehension.•Non-native speakers scored lower for reading enjoyment. This study focuses on the relationship between 15-year-olds’ reading enjoyment and reading comprehension on the one hand and the relationship between these two variables and students’ gender, socio-economic status (SES), and language background on the other. Based on the PISA 2009 literacy test, it includes a secondary analysis of data collected from 4269 Flemish students of which the results were analysed by means of multilevel modelling. The results showed a positive relationship between reading enjoyment and reading comprehension. Girls, higher SES students, and students in the academic track were found to score higher in both reading enjoyment and reading comprehension. Students in the vocational track scored lowest in both reading enjoyment and reading comprehension. Finally, second or additional language (L2) speakers scored lower in reading enjoyment.